Bi-layered/tri-layered bio-media in direct contact with metal diagonal horn for hyperthermia - Singh S.; Sahu B.; Singh S.P. (My University, 2025)
In this paper, theoretical/simulation study of specific absorption rate (SAR) and/or temperature distributions in a bi-layered bio-media (fat and muscle)/realistic tri-layered bio-media (skin, fat, and muscle layers) in direct contact with water-loaded metal diagonal horn (MDH) designed at 915 MHz are investigated. The effects of fat thickness on the input reflection coefficient, reflection coefficient at the interface between the MDH and the bi-layered bio-media, and the SAR distribution in the bi-layered bio-media are also studied through simulation and theoretically at 915 MHz. Further, the SAR parameters such as penetration depth and effective field size inside the bi-layered bio-media due to the MDH are evaluated theoretically and the theoretical results are compared with the corresponding simulation results. Finally, SAR and temperature distributions in tri-layered bio-media without and with embedded irregular/oval-shaped tumor are provided for demonstrating the hyperthermia performance of the MDH applicator. Copyright © Cambridge University Press and the European Microwave Association 2018.